Observation of captive rhinoceros hornbills (Buceros rhinoceros) in Jurong bird park and in 3 Thailand zoos as part of a selection for the re-introduction program of rhinoceros hornbills in Singapore. - Koh, Geraldine Huiping. (2011)
The last record of the existence of rhinoceros hornbills (Buceros rhinoceros) in Singapore was in 1898 (Raffles bulletin of zoology 2007) but the population has since died out. In 2006, a female great pied hornbill (GPH) and a female rhinoceros hornbill (RH) were spotted in a forest in Eng Neo Avenue in Singapore. This triggered off a study by the Singapore Avian Conservation project to pair the female RH with a male RH in 2009 and subsequently lead into the current study of re-introducing the RH in Singapore. In this study, preliminary observations were carried out in JBP to identify the different breeding behaviours of the RH in captivity. After which, based on observations and evaluations, 3 RH, 1 male and 2 females, were selected from a pool of 18 RH captive in 3 Thailand zoos. In the future, these selected candidates would then be imported to Singapore to carry out the next stage of the re-introduction program.